2014
DOI: 10.1111/irv.12254
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of influenza‐associated hospitalizations and outpatient visits in Bangladesh during 2010

Abstract: ObjectiveUnderstanding the costs of influenza-associated illness in Bangladesh may help health authorities assess the cost-effectiveness of influenza prevention programs. We estimated the annual economic burden of influenza-associated hospitalizations and outpatient visits in Bangladesh.DesignFrom May through October 2010, investigators identified both outpatients and inpatients at four tertiary hospitals with laboratory-confirmed influenza infection through rRT-PCR. Research assistants visited case-patients' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 29 publications
5
51
1
5
Order By: Relevance
“…Our results were in keeping with various studies that suggest that indirect costs comprise the bulk of the economic burden associated with influenza illness in middle‐ and high‐income countries 5, 31, 32. Exceptions are occasionally noted in very low‐income countries, such as Bangladesh, where the extremely low remuneration rates for lost work and productivity deflate indirect costs relative to direct costs 24. Additionally, we documented a lower indirect cost for female.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results were in keeping with various studies that suggest that indirect costs comprise the bulk of the economic burden associated with influenza illness in middle‐ and high‐income countries 5, 31, 32. Exceptions are occasionally noted in very low‐income countries, such as Bangladesh, where the extremely low remuneration rates for lost work and productivity deflate indirect costs relative to direct costs 24. Additionally, we documented a lower indirect cost for female.…”
Section: Discussionsupporting
confidence: 91%
“…The burden was particularly heavy on the poorest families, for whom the cost of a single episode of influenza in a family member typically represented more than a tenth of the total household monthly income. The magnitude of the direct costs noted in our study was similar to that found in other low‐ and middle‐income countries among non‐hospitalized (range $4–16) and hospitalized (range $60–575) persons22, 23, 24 and lower than the cost among hospitalized patients in high‐income countries (range $5402–6124) 4, 25, 26…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…30 Higher direct than indirect costs for hospitalization episodes may be attributed to bed rent, food costs, and specialized doctor fees, as frequently more detailed diagnosis is required compared with outpatient care visit. Transportation costs, which we defined as direct costs, are likely higher in rural compared with urban areas, contributing to higher overall direct costs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on influenza infections documented that in Bangladesh more than 50% of the child respiratory infections are caused by influenza viruses (Bhuiyan et al 2014). …”
Section: Resultsmentioning
confidence: 99%